A Porcine Organ-Culture Glaucoma Model Mimicking Trabecular Meshwork Damage Using Oxidative Stress - Snider, Eric J. (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: Re-cellularization of the trabecular meshwork (TM) using stem cells is a potential novel treatment for ocular hypertension associated with glaucoma. To assess the therapeutic efficacy of this approach, improved in vivo and ex vivo models of TM pathophysiology are needed. Here, we investigate whether oxidative stress, induced by hydrogen peroxide (H(2)O(2)), can model glaucomatous ocular hypertension in the readily available porcine anterior segment organ culture model. METHODS: The impact of H(2)O(2) on TM cell viability and function was first evaluated in vitro using primary porcine TM cells. Oxidative stress was then induced by H(2)O(2) infusion into perfused porcine anterior segments. Trabecular meshwork function was assessed by tracking matrix metalloproteinase (MMP) activity and the ability of the preparation to maintain intraocular pressure (IOP) homeostasis after a flow challenge (doubled fluid infusion rate). Finally, the TM was evaluated histologically. RESULTS: H(2)O(2) treatment resulted in a titratable reduction in cellularity across multiple primary TM cell donor strains. In organ culture preparations, H(2)O(2)-treated eyes showed impaired IOP homeostasis (i.e., IOPs stabilized at higher levels after a flow challenge vs. control eyes). This result was consistent with reduced MMP activity and TM cellularity; however, damage to the TM microstructure was not histologically evident in anterior segments receiving H(2)O(2). CONCLUSIONS: Titrated H(2)O(2) infusion resulted in TM cellular dysfunction without destruction of TM structure. Thus, this porcine organ culture model offers a useful platform for assessing trabecular meshwork therapies to treat ocular hypertension associated with glaucoma.